Basketball's record breakers - Frederick, Shane (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2017)
Looks at some of the most famous records in basketball history, including most wins, most points, and most rebounds in a single game.
Includes bibliographical references (page 31) and index.
1040L
Accelerated Reader AR
Keywords: Basketball -- Records -- United States -- Juvenile literature; Basketball players -- Biography -- Juvenile literature